Finding the Root of the Pathos in the Planning System of Iran: 5-why Technique - Elham Vafaei; Gholamreza Geraeinejad (پژوهش‌های برنامه و توسعه)
The main issue in this paper is why the planning system in Iran with more than seven decades of planning experience has not been able to remove the obstacles to accelerate the development. To answer this important question, the pathology of the planning system is examined from two dimensions: Its stages (preparation and compiling (prerequisite, structure, process and product), approval, pre-implementation, implementation and Supervision and evaluation) and its source (inside and outside the organization). Causal relationships between identified disadvantages based on the effectiveness matrix obtained and root disadvantages has been extracted using the 5-Why technique.The results show that the root disadvantages of the planning system are: "Lack of common understanding of concepts by planners, policy makers and implementers", "The rule of centralized and non-participatory methods in planning", "Lack of mechanism for resolving conflicts of interest between program elites", "Rigidity in considering the situation and not paying attention to possible scenarios in the future", "Failure to prepare an action plan and link it to the approved plan", "Existence of sectorial-regional and local orientations in the approval of programs", "Relying on government resources and not paying attention to internal and external capacities and resources", "Lack of attention of the planning system to the system of reform and adjustment in policies, goals and executive plans after monitoring and evaluation" and "severe weakness of regulatory mechanisms". Also, suggestions have been made to policy makers and planners to design an optimal planning system.The results show that "Lack of common understanding of concepts by planners, policy makers and implementers", "The rule of centralized and non-participatory methods in planning", "Lack of mechanism for resolving conflicts of interest between program elites", "Stable in considering the situation and not paying attention to possible scenarios in the future", "Failure to prepare an action plan and link it to the approved plan", "Existence of sectoral-regional and local orientations in the approval of programs", "Relying on government resources and not paying attention to internal and external capacities and resources", "Lack of attention of the planning system to the system of reform and adjustment in policies, goals and executive plans after monitoring and evaluation" and "severe weakness of regulatory mechanisms" are the root damage of the planning system. Also, suggestions have been made to policy makers and planners to design an optimal planning system.